Essential cataloguing - Bowman J H (London Facet, 2003)
This book covers descriptive cataloguing & is designed as a simple companion to the AACR( revised 2002 edition). It concentrates on the basics including many references to other formats. The author leads through the cataloguing process, covering descript
Keywords: Cataloguing